The Obstacles Faced in Presenting ESP Procedure Text through Oral Presentation in the Business and Marketing Major - Siagian, Khairul Azmi; Sri Hartiningsih (BABASAL English Education Journal, 2024)
This study aimed to investigate the obstacles faced when presenting ESP procedure text through oral presentations in business and marketing majors and how to overcome those obstacles. This study used a case study design to understand the whole case in the totality of the environment. The subject of this study was an English teacher in a private Vocational High School (VHS) majoring in business and marketing in West Java, Indonesia. This study used two data collection techniques: observation and interview. The data was analyzed using thematic analysis. This study reported that there were several obstacles faced, such as the lack of students' readiness in presenting ESP procedure text through oral presentation (lack of confidence and lack of language mastery), lack of teacher's readiness in handling ESP teaching, and the mismatch between the given curriculum and the business and marketing students' need. Further, there were also several alternative solutions to overcome those obstacles, such as modifying the material and instructional model based on student's needs, using additional educational tools, and watching students' progress in preparing their oral presentations.